IMPLEMENTASI PP. NO. 48 TAHUN 2014 ANTARA REGULASI DAN PRAKTIK (Studi Kasus di Kabupaten Konawe dan Kota Semarang) (Harmoni, 2016)
The new regulations on marriage cost as mandated by Government Regulation No. 48 of 2014 explaines that the service charge of marriage at the KUA is zero rupiah, and 600,000 rupiahs if the marriage is conducted outside the office. However, the practice is different in different regions. This study was conducted to determine the implementation of the regulation. Beside that, this study was held to find out the response of the Muslim leaders and people, as well as the constraints faced by the officers and the public. By using qualitative methods, this research builds three main findings. Firstly, the regulation has largely been done by the Ministry of Religious Affairs of the Konawe and the city of Semarang and the Minstry of Religious in Regency or City. Secondly, KUA officials with this PP should feel duties and functions, as has been set out clearly the cost of marriage at KUA and outside the office of Rp600,000. And thirdly, the factors that limit the implementation of this regulation is the community itself. They put more trust to the Imam in their hometown in Konawe and modin in Semarang in administering their marriage cost. As a result, the service charge of marriage becomes more expensive because there have to pay additional charges beyond a predetermined fee.
Keywords: Modin; Imam Kampung; PP No 48 of 2014; Cost of Marriage; Biaya Nikah